Os sistemas agroflorestais integrados (SAF’s) como alternativas para o desenvolvimento sustentável da agricultura familiar na região do Cariri cearense - Nascimento, Francisco das Chagas Barbosa do (2022)
We sought to highlight the pioneering spirit of the Base Christian Association (ACB) for more than four decades in promoting agroecological agriculture, through integrated agroforestry systems (SAF's) in the Cariri region of Ceará. As objectives, we sought to develop a comparative and evaluative study on the actions of this institution and its contributions to the development of agro-sustainable agriculture in the localities of Baixa do Maracujá in Crato, Lagoa dos Patos and Mamãos in Nova Olinda Ceará. Based on the information collected, an attempt was made to demonstrate the economic-environmental viability of SAF's as elements that potentially generate income and improve the quality of life in the researched locations and region. The research was based on the participatory research method, of a qualitative-quantitative nature, with the sample universe composed of nine farmers, their families and respective locations, where two of these farmers work with SAF's and the others with traditional agriculture. The criterion for choosing the areas was because they are located in a transition zone between the plateau and the semi-arid, in an important region of the interior of the Northeast, in addition to using agroecological techniques disseminated by the Association Christian de Base. I used mixed questionnaires, with a total of 20 questions, which were audio-recorded and transcribed in the thesis. The collected information dealt with some aspects of the properties, the actions of environmental preservation linked to the production, the commercialization of the products and the gain of quality of life of the peasants. As measurable results, it was noticed that: the entire surveyed area comprises 19 hectares, approximately 190,000 m2, of which only 4 hectares are agrosustainable areas, corresponding to 40,000 m2. It is also noteworthy that agroforestry companies have an average monthly income of 67.9% higher than those of traditional agriculture, making it clear that the SAF's are consolidated as the best alternative for the agricultural development of small and medium-sized properties in the Cariri region cearense, mainly because they allow the diversification of species: grasses, legumes, vegetables, fruit trees and forestry integrated to the creation of small and medium-sized animals, always obeying the system of respect and environmental preservation that are always so necessary.